Threshold singularities in Higgs boson production and decay - Palisoc, Caesar P. (2000)
At the one-loop level, the problem of threshold singularities in Higgs boson production and decay is proposed to be resolved by the implementation of two independent measures. The first one is by treating the weak vector bosons circulating in the loop diagrams to be unstable particles as well. This treatment is adopted individually to the decay of the Higgs boson to fermion pair and W boson pair at one-loop, providing a finite estimate for the width at thresholds that are otherwise negatively infinite. The second one is by dealing with the problem in the context of the complex pole framework of defining the width of an unstable particle. In defining the width of the Higgs boson on the basis of the complex pole of the propagator, a full width at one-loop level free of threshold singularities is obtained. In this measure, the width of the Higgs boson itself acts as the regulator of the singularity at threshold.
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
"April 2000."
Thesis (Ph.D. Physics)--University of the Philippines Diliman.
Keywords: Higgs bosons